2004
DOI: 10.1056/nejmoa043555
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antibody Responses after Intradermal Vaccination against Influenza

Abstract: As compared with an intramuscular injection of full-dose influenza vaccine, an intradermal injection of a reduced dose resulted in similarly vigorous antibody responses among persons 18 to 60 years of age but not among those over the age of 60 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
211
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(225 citation statements)
references
References 16 publications
13
211
1
Order By: Relevance
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In transplant patients, low dose intradermal vaccines (3-6 lg) have not demonstrated significant benefit when compared to standard vaccination, or when administered as a booster dose following IM vaccination (8,17). Studies in immunocompetent people ages 18-59 have demonstrated that seroconversion rates with 15 lg of intradermal antigen range from 56-79% for each specific vaccine strain (18)(19)(20). In contrast, in our study, seroconversion to each specific vaccine strain following ID vaccination ranged from 21.5% to 37.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports point out the advantage of i.d. vaccination in humans as a dose-sparing strategy as well as the potential for increasing immunogenicity to certain vaccine Ags (1)(2)(3). This is of particular interest to populations that may not mount sufficiently protective immune responses to traditional vaccines, such as the elderly, young infants, and the immunocompromised (4 -7).…”
mentioning
confidence: 99%